A Review of Untangling Critical Race Theory - Hatch, John B. (Christian scholar's review, 2025)
Untangling Critical Race Theory: What Christians Need to Know and Why It Matters Ed Uszynski Published by IVP in 2024 272pp / $17.57 / 978-1514004814 Amazon Goodreads Over the past five years, Christians have had much to say about Critical Race Theory (CRT). Unfortunately, the most widely heard voices have tended to favor demonizing over...